The Effect of Shadowing Technique Towards Students’ Speaking Skill at the Eleventh Grade Students of SMAN 1 Cihara in Academic Year 2023/2024 - Belinda Yulistia; Rizdki Elang Gumelar; Riandi Riandi (Journal of English Education Studies, 2025)
This research paper aims to determine the Effect of Shadowing Technique Towards Students’ Speaking Skills at the Eleventh Grade Students of SMAN 1 Cihara Lebak-Banten. This study uses a quantitative approach with a quasi-experimental design research method, which uses three concepts, namely pre-test, treatment, and post-test. The population was 93 students and the sample of this study was 64 students consisting of 32 students in the experimental class and 32 students in the control class. The results of the post-test for both the experimental and control classes, after receiving treatment, the results of the experimental class were 2215 and the control class was 2175, meaning that the results of the experimental class were higher than the control class. Based on the data above, the shadowing technique showed better results in the experimental class than in the control class.